The Impact of Age, Educational Background, Gender, and Monthly Expenditure on the Potential of Green Products Buyers - Abdurachman, Edi; On, Khi (International Research Journal of Business Studies, 2011)
The level of environmental degradation continues rising to lead a global warming. Without immediate prevention measures, this could bring the Earth into total breakdown. Therefore environmental preservation campaign buzzing for every element of the society to participate in the campaign. Number of people understand and care about environmental degradation and global warming is growing. Many people aim is to influence the lifestyle and consumption pattern of the society. The campaign is to attract and motivate the society to purchase environmentally friendly goods which are also known as green products. The number of potential people to the purchase green products continues rising along with the spread of knowledge concerning the importance of conserving the environment. Such condition recognized by the companies. Therefore they start to consist them as the target market. One of the important marketing aspects is market segmentation. There are many ways and statistical methods to classifying consumers into particular segmentations; one of the methods is the Chi-squared Automatic Interaction Detector (CHAID). CHAID, it is implemented in this research for green product market segmentation (Segmentation result subsequently used to determination of the following strategic marketing measures). CHAID examines independent variables used in classification and arrangement process based on the level of chi-square statistical significance towards the dependent variable. Dependent variable used in this research is potential customer trend to purchase preference of green products. The result shows that significantly influential variables towards the potential of green products buyers are age, educational background, gender and their monthly amount of expenditure / spending.